Effect of weed control methods and sulphur fertilization on growth and yield of groundnut - Pancholi, Pinki; Yadav, S.S.; Verma, H.P.; Meena, J.S.; Yadav, L.R.; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted at Agronomy Farm, S.K.N. College of Agriculture, Jobner(Rajasthan) during kharif season of 2013. Results showed that application of pendimethalin at 0.75kg ha–1 and one HW at 25 days after sowing (DAS) resulted in significant reduction in weed density,weed infestation and weed dry matter in comparison to most of the treatments. The further resultsindicated that weed free plots showed significantly higher dry matter accumulation, dry weight ofnodules per plant, number of pods per plant but number of kernels per pod, seed index, pod yieldand haulms yield, remained at par with the application of pendimethalin @ 0.75 kg ha–1. The weedfree plot showed significantly higher number of nodules per plant, fresh weight of nodules perplant and remained at par with application pendimethalin @ 0.75 kg ha–1 and one hand weeding at25 DAS over control. But, weed free plot significantly increased shelling percentage and remainedat par with application @ 0.75 kg ha–1, one hand weeding at 25 DAS and imazethapyr @ 100 g ha–1over control. Result further indicated that application of sulphur @ 60 kg ha–1 significantly higherweed dry matter, dry matter accumulation, dry and fresh weight of nodules, number of nodules perplant, number of pods per plant, number of kernels per pod, seed index, pod yield and haulmsyield and shelling percentage over control. However, harvest index, weed density and weedinfestation remained materially unchanged under different treatments of weed control and sulphurlevels.